High Expression of Glycolytic Genes in Cirrhosis Correlates With the Risk of Developing Liver Cancer - Lee, Nathan C. W.; Carella, Maria Annunziata; Papa, Salvatore; Bubici, Concetta (Frontiers in Cell and Developmental Biology, 2018)
A marked increase in the rate of glycolysis is a key event in the pathogenesis of hepatocellular carcinoma (HCC), the main type of primary liver cancer. Liver cirrhosis is considered to be a key player in HCC pathogenesis as it precedes HCC in up to 90% of patients. Intriguingly, the biochemical events that underlie the progression of cirrhosis to HCC are not well understood. In this study, we examined the expression profile of metabolic gene transcripts in liver samples from patients with HCC and patients with cirrhosis. We found that gene expression of glycolytic enzymes is up-regulated in precancerous cirrhotic livers and significantly associated with an elevated risk for developing HCC. Surprisingly, expression levels of genes involved in mitochondrial oxidative metabolism are markedly increased in HCC compared to normal livers but remain unchanged in cirrhosis. Our findings suggest that key glycolytic enzymes such as hexokinase 2 (HK2), aldolase A (ALDOA) and pyruvate kinase M2 (PKM2) may represent potential markers and molecular targets for early detection and chemoprevention of HCC.